Rural development and transformation of the rice sector in Myanmar: Introduction of best management practices for sustainable rice agriculture - Wehmeyer, Helena; Malabayabas, Arelene; San, Su Su; Thu, Aung Myat; Tun, Myat Su; Thant, Aye Aye; Connor, Melanie (SAGE Publications, 2022)
Myanmar has experienced considerable economic and social changes since its political transition in the early 2010s. Its agriculture sector has demonstrated rapid intensification and modernization. Agricultural best management practices (BMPs), e.g., drum seeders and laser land levelling, were introduced to rice farmers in Bago Region in 2012 to increase sustainable production and counter negative environmental impacts. The objective of this study was to determine the socioeconomic and agronomic changes due to the adoption of BMPs between adopters and non-adopters. Using a digital survey questionnaire application to collect household data, 200 farmers in eight villages were interviewed in 2012 and 2017. Data were analysed using uni- and multivariate statistics. Mediation analysis was utilized to evaluate the effect of the farmer group on rice yields. Overall, all farmers in this study experienced substantial positive changes over the course of five years in line with the national development efforts. Differences among adopters and non-adopters were not significant, but notable distinctions existed between cropping patterns. Rice-pulse farmers had higher yields ( + 0.4 t/ha), yet rice-rice farmers had larger cultivation areas, received higher agricultural credits, and had superior income levels. Nevertheless, rice yields remained low (<4 t/ha). Education was found to be an important predictor of yield. Hence, this factor is crucial for accelerating agricultural development in Myanmar. Improving extension services and knowledge transfer are necessary to expand the dissemination of sustainable BMPs and make farmers more resilient against the negative implications of climate change.